Minimum effective dose of chlorantraniliprole and chromafenozide to control oil palm bunch moth Tirathana mundella walker - Jie, Patricia Hung King; Chong, Ming Su; Yee, Min Kwan; Ab Aziz, Zakry Fitri; Kian, Huat Ong (UNIMAS Publisher, 2021)
The bunch moth, Tirathaba mundella is one of the leading pests in oil palm estates established on peatland. Severely infested male inflorescences usually would fail reaching anthesis. Reduction in the number of inflorescences at anthesis stage would suggest less food source and breeding ground for oil palm pollinating weevils, Elaeidobius kamerunicus, thus, affecting the fruiting percentage of oil palm and its yield. Despite to be less detrimental to the environment, biopesticide usages in the field is losing favour due to its slower rate of kill compared with conventional chemical pesticides, shorter persistence in the environment and susceptibility to unfavourable environmental conditions. The use of high host specificity chemical pesticides, such as chlorantraniliprole and chromafenozide are gaining popularity in pest management regimes. In this study, the optimum dose for chlorantraniliprole and chromafenozide in controlling T. mundella was assessed to provide valuable information for sustainable oil palm pest management. Several dosages of pesticide were evaluated for their effectiveness against T. mundella in a 7-year-old oil palm estate for six months. Based on the results obtained, application of 30 g or 40 g active ingredient (a.i.) per ha chlorantraniliprole were recommended to provide the longest protection period. To make plan for an effective pest management that could reduce material and labour cost per ha as well as the risks in developing pesticide resistance among pest, 30 g a.i per ha of chlorantraniliprole is recommended to be rotated with 25 g a.i. per ha chromafenozide for a total of four rounds in a year.